Rancang Bangun Pengendali Pintu Air Sungai Dengan Menggunakan Logika Fuzzy dan Simple Additive Weighting - Adven Edo Prasetya; Mochammad Hannats Hanafi; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Flooding becomes a problem that still can not be solved. Flood problems almost always occur in some areas in Indonesia, especially during the rainy season. If rain falls with high rainfall, and the river can not accommodate the rainfall, there will be flooding. To regulate and maintain the river water flow so as not to overflow and cause flooding, the river flow used water gates. In this study the authors will do the design of the water gate controller system using Fuzzy logic and Simple Additive Weighting. Fuzzy logic in this research will be used to determine the size of water gate opening based on surface water level data obtained from the acquisition of water level sensors, and rainfall data, obtained from the acquisition of rain module sensor. As the actuator to drive the gate is used servo motor. Data from the acquisition of the sensor will be sent to Arduino Mega 2650, then on the microcontroller, Fuzzy Logic calculation is done and Simple Additive Weighting method. Overall Fuzzy logic calculation on the Main River and the entire Anak River has a percentage error of 0.09875%, while the calculation of SAW method used to determine the tributaries that become the best alternative, there is no difference between manual calculations and calculations performed by the system.